Prevalence and factors associated with frailty and pre-frailty in the older adults in China: a national cross-sectional study - Zeng, Xue-zhai; Meng, Ling-bing; Li, Ying-ying; Jia, Na; Shi, Jing; Zhang, Chi; Hu, Xing; Hu, Jia-bin; Li, Jian-yi; Wu, Di-shan; Li, Hui; Qi, Xin; et al. (Frontiers in Public Health, 2023)
Objective Frailty increases poor clinical outcomes in older adults, the aim of this study was to investigate the prevalence and factors associated with frailty and pre-frailty in older adults in China. Research design and methods Data were obtained from the Sample Survey of the Aged Population in Urban and Rural China in 2015, which was a cross-sectional study involving a nationally representative sample of older adults aged 60 years or older from 31 provinces/autonomous regions/municipalities in mainland China. The frailty index (FI) based on 33 potential deficits was used to classify individuals as robust (FI < 0.12), pre-frail (FI ≧0.12 and <0.25) and frail (FI ≥0.25). Results A total of 208,386 older people were included in the study, and the age-sex standardised prevalence of frailty and pre-frailty among older adults in China was 9.5% (95% CI 9.4–9.7) and 46.1% (45.9–46.3) respectively. The prevalence of frailty and pre-frailty was higher in female than in male older adults, higher in rural than in urban older adults, and higher in northern China than in southern China. The multinomial analysis revealed similar risk factors for frailty and pre-frailty, including increased age, being female, living in a rural area, low educational attainment, poor marital status, living alone, difficult financial status, poor access to medical reimbursement, and living in northern China. Conclusion Frailty and pre-frailty are very common among older adults in China and differ significantly between southern and northern China, men and women, and rural and urban areas. Appropriate public health prevention strategies should be developed based on identified risk factors in frail and pre-frail populations. The management of frailty and pre-frailty should be optimised according to regional and gender differences in prevalence and associated factors, such as strengthening the integrated management of chronic diseases, increasing reimbursement rates for medical costs, and focusing on vulnerable groups such as the disabled, economically disadvantaged, living alone and those with low literacy levels, in order to reduce the burden of frailty among older adults in China.